2002
DOI: 10.1186/1476-511x-1-3
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: BackgroundThe lack of certain essential polyunsaturated fatty acids (PUFAs) induces perturbation in cell proliferation, apoptosis and dedifferentiation that could be linked to an increased protumorigenic trend. Contrarily, n-3 essential fatty acids (EFAs) arrest cell proliferation in several tumor models. According to the concept of field cancerization, multiple patches of abnormal epithelial proliferation may coexist in the vicinity of oropharyngeal neoplasms.The purpose of the present study is to determine w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…)[ 20 ], have been reported to suppress inflammation, oxidative stress and cancer risk in animal study [ 21 ] and observational study [ 22 ]. Additionally, Actis et al[ 23 ] found dietary lipids (especially for n-3 fatty acids) also reduced cell proliferation and differentiation of murine oral squamous epithelium. Therefore, these have been reasonably hypothesized that fish consumption may lower the risk of oral cancer.…”
Section: Discussionmentioning
confidence: 99%
“…)[ 20 ], have been reported to suppress inflammation, oxidative stress and cancer risk in animal study [ 21 ] and observational study [ 22 ]. Additionally, Actis et al[ 23 ] found dietary lipids (especially for n-3 fatty acids) also reduced cell proliferation and differentiation of murine oral squamous epithelium. Therefore, these have been reasonably hypothesized that fish consumption may lower the risk of oral cancer.…”
Section: Discussionmentioning
confidence: 99%